GAMBARAN ANGKA KEJADIAN KARIES PADA ANAK SEKOLAH DASAR DI INDONESIA (Politeknik Kesehatan Kemenkes Bandung, 2020)
ABSTRACT Caries is a disease in the oral cavity due to bacterial interactions that convert carbohydrates in food to acids through the fermentation process and is caused by many factors such as host (teeth), microorganisms (bacteria), substrate (carbohydrate), and time. According to the results of the Basic Health Research (RISKESDAS) in 2018 that the prevalence of caries in Indonesia is very high at 88.8%. The purpose of this study was to find out the depiction of caries incidence rates in primary school children in Indonesia based on age, Knowing the depiction of caries incidence rates in primary school children in Indonesia based on Gender. This type of research is a literature study by finding relevant references and library materials. with the content analysis method. Descriptive analysis method is done by describing the facts obtained, then analyzed and not only described but provides sufficient understanding and explanation. Based on the results of the Literature Study, the average respondent who experienced caries based on sex in boys (49.5%), girls (42.8%). Caries by Age 6-10 (21.2%). So the conclusion is based on some research results on the description of the incidence of caries in primary school children in Indonesia is the highest rate of caries experience in boys (49.4%). And at the age of 6-10 years (21.2%). Keywords : Dental Caries, Primary school children